Musculoskeletal Complaints Reviewed from an Ergonomic Aspect - Hubban Fathani Manik; Nurhayati Nurhayati; Syafran Arrazy; Susilawati Susilawati (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
Musculoskeletal complaints are pain experienced in the joints, nerves, tissues, muscles, and the spinal column, often resulting from prolonged static postures, work postures, and repetitive movements. The objective of this study was to analyze ergonomic factors that influence musculoskeletal disorders (MSDs) among office workers. This research employed a quantitative approach with a cross-sectional design. The study population consisted of administrative workers, with a sample of 42 respondents. Data were collected through questionnaires to measure the duration of static postures and repetitive movements, the Rapid Office Strain Assessment (ROSA) instrument to evaluate working postures, and the Nordic Body Map (NBM) to assess musculoskeletal complaints. The results indicated that the majority of respondents (66.7%) engaged in static postures for more than one hour per day. The variable of duration working in static postures showed a significant p-value of 0.014, indicating a statistically significant effect on the incidence of MSDs. The Odds Ratio (Exp(B)) was 10.205, suggesting that workers who maintain static postures for more than one hour are 10.2 times more likely to experience musculoskeletal complaints compared to those with static postures lasting one hour or less. The variable of working posture yielded a p-value of 0.008, demonstrating a significant influence of working posture on MSDs. The Odds Ratio (Exp(B)) was 12.135, indicating that workers with hazardous working postures have a 12.1 times higher risk of experiencing MSDs compared to those with non-hazardous postures. It is recommended that workers avoid prolonged static postures to maintain the health of the musculoskeletal system.